The Dubious Link - ARIEL C. ARMONY (stanford university, 2004)
This book explores the question of whether and how civil society inï¬‚uences democracy, showing that the link between them is neither necessary nor universalâ€”as many others have claimed. I argue that civil society has a â€œdark sideâ€ (i.e., a nondemocratic face) and that the speciï¬c sociohistorical context determines the nature of civic participation and its potential effect on democracy. I claim that institutions, the law, and dominant patterns of social interaction structure the conditions in which individuals organize.